Peran Kecerdasan Emosi terhadap Quarter Life Crisis pada Mahasiswa Tingkat Akhir - Rifka Fatchurrahmi; Siti Urbayatun (Jurnal Psikologi Teori dan Terapan, 2022)
Abstract: Final year students enter the developmental age of young adults. Individuals who enter young adulthood will face various problems in completing studies and other problems. Individuals can experience a quarter-life crisis which is characterized by emotional responses such as feelings of panic, helplessness, instability, anxiety, depression and even depression. This can be influenced by various causes, one of which is emotional intelligence. The purpose of this study was to examine the role of emotional intelligence on the quarter life crisis in final year students. Data were obtained from a sample of 125 final year students using purposive and simple random techniques. The instruments used for data collection are the quarter life crisis scale and the emotional intelligence scale. Data were analyzed using simple linear regression method. The results of the study found that emotional intelligence played a significant role in the quarter life crisis in final year students. Aspects of emotional intelligence, are self-motivation, empathy and social skills play a role in the quarter-life crisis. Meanwhile, aspects of self-awareness and self-regulation do not play a role in the quarter life crisis. Abstrak: Mahasiswa tingkat akhir masuk dalam perkembangan usia dewasa muda. Individu yang memasuki usia dewasa muda akan menghadapi berbagai permasalahan dalam penyelesaian studi maupun masalah lainnya. Individu dapat mengalami quarter-life crisis yang ditandai dengan respon emosional seperti perasaan panik, tidak berdaya, tidak stabil, kecemasan, tertekan bahkan depresi. Hal tersebut dapat dipengaruhi oleh berbagai penyebab salah satunya kecerdasan emosi. Tujuan dari penelitian ini adalah untuk menguji peran kecerdasan emosi terhadap quarter life crisis pada mahasiswa tingkat akhir. Data diperoleh dari sampel sebanyak 125 mahasiswa tingkat akhir menggunakan teknik purposive dan simple random. Instrumen yang digunakan untuk pengambilan data adalah skala quarter life crisis dan skala kecerdasan emosi. Data dianalisis menggunakan metode regresi linier sederhana. Hasil penelitian menemukan bahwa kecerdasan emosi berperan signifikan terhadap quarter life crisis pada mahasiswa tingkat akhir.